(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
In this article, integrative methods of teaching "General Chemistry" of Food Technology students are given, and the process of integrating food chemistry, biochemistry and physical chemistry into chemistry is carried out. Also, the integration of dark sciences was studied as a research for three years. The results of the tests were conducted mainly in the form of test control of students. The results showed that the indicator in the experimental groups was higher than in the control groups, it was determined by mathematical and statistical calculations. It was recommended that the integration of experts in this field in the process of training will be of great importance in the professional activities of future engineers-technologists.